A Novel Noninvasive Patient-Specific Navigation Method for Orbital Reconstructive Surgery: A Phantom Study Using Patient Data. Issue 3 (March 2019) - Lee, Jeonghwan; Mekuria, Kinde; Son, Tae-geun; Jeong, Woo Shik; Choi, Jong Woo; Kim, Youngjun
Abstract : Background: The correction of orbital deformities is an ongoing challenge in maxillofacial surgery. Computer-assisted navigation can improve surgical outcomes. However, conventional registration methods for navigation are not appropriate for orbital reconstructive surgery. This study proposes an accurate, noninvasive, patient-specific navigation method and demonstrates its feasibility. Methods: A noninvasive, patient-specific registration frame based on the external auditory canals and upper front teeth was designed using software developed in-house. A three-dimensional craniofacial model was segmented from patient computed tomographic data for the registration frame. A customized craniofacial phantom was also made using this three-dimensional model, with 20 embedded target points on the orbital model and 21 landmark points on the reference standard model. The proposed method was compared with two conventional registration methods: the dental splint–based method and the invasive marker frame–based method. Twenty trials were conducted for evaluation. Target registration error and surface registration error were computed to measure accuracy. Results: The proposed method showed a target registration error of 1.05 ± 0.52 mm, with greater accuracy than conventional methods (dental splint, 2.10 ± 0.63 mm; invasive marker frame, 1.22 ± 0.46 mm). The proposed method yielded the best results for surface registration error, with 0.38 mm of deviation (dental splint, 0.82 mm; invasive marker frame, 0.60 mm). Conclusion: The proposed noninvasive patient-specific registration method demonstrated superior results for both target registration error and surface registration error compared with other conventional registration methods for computer-assisted navigation in orbital reconstructive surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.